1992
DOI: 10.1073/pnas.89.5.1899
|View full text |Cite
|
Sign up to set email alerts
|

Dark induction of zeaxanthin-dependent nonphotochemical fluorescence quenching mediated by ATP.

Abstract: Zeaxanthin-dependent nonphotochemical fluorescence quenching is a light-induced activity in plants that apparently protects against the potentially damaging effects of excess light. We report a dark-induced nonphotochemical quenching in thylakoids of Lactuca satva L. cv. Romaine mediated by ATP. This effect is due to low lumen pH from hydrolysis-dependent proton pumping and hence required an active ATPase. The induction was optimal at 0.3 mM ATP, a physiological concentration, and occurred under conditions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
1
3

Year Published

1994
1994
2006
2006

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(90 citation statements)
references
References 41 publications
(99 reference statements)
3
83
1
3
Order By: Relevance
“…Moreover, this different capacity to generate a sustained nonphotochemical quenching in the light cannot be ascribed to the presence of a quenched state generated before illumination, which would originate from a trans-thylakoid ∆pH established by ATP hydrolysis in darkness. Indeed, uncoupling of dark-adapted Chlamydomonas cells by ionophores had no effect on the variable fluorescence, in contrast to plants placed in conditions where high-energy state quenching is induced in the dark (41).…”
Section: Characteristics Of Nonphotochemical Quenching In Chlamydomonasmentioning
confidence: 87%
“…Moreover, this different capacity to generate a sustained nonphotochemical quenching in the light cannot be ascribed to the presence of a quenched state generated before illumination, which would originate from a trans-thylakoid ∆pH established by ATP hydrolysis in darkness. Indeed, uncoupling of dark-adapted Chlamydomonas cells by ionophores had no effect on the variable fluorescence, in contrast to plants placed in conditions where high-energy state quenching is induced in the dark (41).…”
Section: Characteristics Of Nonphotochemical Quenching In Chlamydomonasmentioning
confidence: 87%
“…From this and other evidence it is widely concluded that the effect of low pH is due to protonation-induced conformational changes in one or more of the components of the PSII antenna Gilmore and Yamamoto 1992;Noctor et al, 1993;Ruban et al, 1993;Bilger and Bjö rkman, 1994). Support for the view that both protonation and zeaxanthin induce conformational changes in the PSII antenna came later from an analysis of fluorescence lifetimes (Gilmore et al, 1995(Gilmore et al, , 1996a(Gilmore et al, , 1996b and steadystate fluorescence (Walters and Horton, 1993), which indicated that the qE was associated with a switch from an unquenched to a quenched conformation.…”
Section: Discussionmentioning
confidence: 99%
“…quenching of chlorophyll fluorescence (Horton and Bowyer, 1990;Krause and Weis, 1992) has shown that it is dependent on the acidification of the thylakoid lumen that results from light-induced proton translocation (Briantais et al, 1979 ;Gilmore and Yamamoto, 1992). This implies that protonation of pigments or amino-acid residues is a key event in the induction of qE.…”
Section: -(34-dichlorophenyl)-ll-dimethylurea; Lhci Light-harvestingmentioning
confidence: 99%